Od sjużetu do plotu (i z powrotem) - Brzostowska-Tereszkiewicz, Tamara (Przegląd Rusycystyczny, 2010)
FROM SYUZHET TO PLOT (AND BACK AGAIN) Summary The subject of the present paper is the evolution of the Russian Formalists’ ‘syuzhet/fabula’ opposition in Polish and Anglo-American literary studies. A comparative analysis of a number of Polish and English translations shows that the transference of original terminology across interlingual and interdiscursive borders resulted in theoretical shifts, methodological aber-rations and historical misinterpretations of the source concept. The discussed translations not only contributed to constructing the one-sided image of the “Russian Formalist School” in target discourses, but also established new lexicons of literary studies. Terminological translocations are treated as exponents and factors of the evolution of literary theory. ПРЕОБРАЗОВАНИЕ CЮЖЕТА В PLOT (И ОБРАТНО) Резюме Предметом настоящей статьи является эволюция формалистической оппозиции „фабулы” и „сюжета” в польском и англо-американском литературоведении. Сравнительный анализ нескольких польских и английских научных переводов показывает, что перемещение оригинальной терминологии через междуязычные и междискурсивные границы вызвало теоретические сдвиги, методологические аберрации и исторически неправильное толкование источника. Рассматриваемые тексты не только способствовали формированию одностороннего образа „русской формальной школы” в воспринимающих дискурсах, но даже устанавливали новые литературоведческие лексиконы. Терминологические смещения рассматриваются как показатели и факторы литературоведческой эволюции.